Answer:
625.25
Step-by-step explanation:
the answer is 625.25
420 cents for 1000 g. So 42 cents for 100 g (i crossed multiplied).
%profit=63-42/42 *100=50%
Answer:
<u><em>k = 0.2645</em></u>
Step-by-step explanation:
Given model:
y = 4070 ![e^{kt}](https://tex.z-dn.net/?f=e%5E%7Bkt%7D)
y = no. of hits website received = 9000 (in 3rd month)
t= no. of months website has been operational = 3
put in the above equation:
9000 = 4070 ![e^{3k}](https://tex.z-dn.net/?f=e%5E%7B3k%7D)
= ![e^{3k}](https://tex.z-dn.net/?f=e%5E%7B3k%7D)
=![e^{3k}](https://tex.z-dn.net/?f=e%5E%7B3k%7D)
<u><em>Taking natural logarithm on both sides, we get:</em></u>
=![ln(e^{3k})](https://tex.z-dn.net/?f=ln%28e%5E%7B3k%7D%29)
= 3k ln<em>e</em>
ln<em>e</em>=1
= 3k
or k = ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
![ln\frac{900}{(407)}](https://tex.z-dn.net/?f=ln%5Cfrac%7B900%7D%7B%28407%29%7D)
k =
(0.7936)
<em>k = 0.2645</em>
<em />
Answer:
![3 + 12 + 48 + 192 + 768 = \sum\limits^4_{n=0} 3 * 4^n](https://tex.z-dn.net/?f=3%20%2B%2012%20%2B%2048%20%2B%20192%20%2B%20768%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%203%20%2A%204%5En)
![4 + 32 + 256 + 2048 + 16384 = \sum\limits^4_{n=0} 4 * 8^n](https://tex.z-dn.net/?f=4%20%2B%2032%20%2B%20256%20%2B%202048%20%2B%2016384%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%204%20%2A%208%5En)
![2 + 6 + 18 + 54 + 162 = \sum\limits^4_{n=0} 2* 3^n](https://tex.z-dn.net/?f=2%20%2B%206%20%2B%2018%20%2B%2054%20%2B%20162%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%202%2A%203%5En)
![3 + 15 + 75 + 375 + 1875 = \sum\limits^4_{n=0} 3* 5^n](https://tex.z-dn.net/?f=3%20%2B%2015%20%2B%2075%20%2B%20375%20%2B%201875%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%203%2A%205%5En)
Step-by-step explanation:
Given
See attachment for complete question
Required
Match equivalent expressions
Solving (a):
![3 + 12 + 48 + 192 + 768](https://tex.z-dn.net/?f=3%20%2B%2012%20%2B%2048%20%2B%20192%20%2B%20768)
The expression can be written as:
--- 0
---- 1
--- 2
---- 3
---- 4
For the nth term, the expression is:
---- n
So, the summation is:
![3 + 12 + 48 + 192 + 768 = \sum\limits^4_{n=0} 3 * 4^n](https://tex.z-dn.net/?f=3%20%2B%2012%20%2B%2048%20%2B%20192%20%2B%20768%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%203%20%2A%204%5En)
Solving (b):
![4 + 32 + 256 + 2048 + 16384](https://tex.z-dn.net/?f=4%20%2B%2032%20%2B%20256%20%2B%202048%20%2B%2016384)
The expression can be written as:
--- 0
---- 1
--- 2
---- 3
---- 4
For the nth term, the expression is:
---- n
So, the summation is:
![4 + 32 + 256 + 2048 + 16384 = \sum\limits^4_{n=0} 4 * 8^n](https://tex.z-dn.net/?f=4%20%2B%2032%20%2B%20256%20%2B%202048%20%2B%2016384%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%204%20%2A%208%5En)
Solving (c):
![2 + 6 + 18 + 54 + 162](https://tex.z-dn.net/?f=2%20%2B%206%20%2B%2018%20%2B%2054%20%2B%20162)
The expression can be written as:
--- 0
---- 1
--- 2
---- 3
---- 4
For the nth term, the expression is:
---- n
So, the summation is:
![2 + 6 + 18 + 54 + 162 = \sum\limits^4_{n=0} 2* 3^n](https://tex.z-dn.net/?f=2%20%2B%206%20%2B%2018%20%2B%2054%20%2B%20162%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%202%2A%203%5En)
Solving (d):
![3 + 15 + 75 + 375 + 1875](https://tex.z-dn.net/?f=3%20%2B%2015%20%2B%2075%20%2B%20375%20%2B%201875)
The expression can be written as:
--- 0
---- 1
--- 2
---- 3
---- 4
For the nth term, the expression is:
---- n
So, the summation is:
![3 + 15 + 75 + 375 + 1875 = \sum\limits^4_{n=0} 3* 5^n](https://tex.z-dn.net/?f=3%20%2B%2015%20%2B%2075%20%2B%20375%20%2B%201875%20%3D%20%5Csum%5Climits%5E4_%7Bn%3D0%7D%203%2A%205%5En)
If the equation is let's say 3x+ 7 +4x to combine like terms, you would take 3x and 4x since they both have x. You wouldn't take the 7 since it doesn't have and x like the other numbers. 3x +4x = 7x so your new equation would be 7x + 7.